Multispectral optoacoustic tomography to differentiate between lymph node metastases and coronavirus‐19 vaccine‐associated lymphadenopathy. (18th January 2023) - Placke, Jan‐Malte; Mertens, Delphine; Tasdogan, Alpaslan; Chorti, Eleftheria; Schadendorf, Dirk; Ugurel, Selma; Roesch, Alexander; Stoffels, Ingo; Klode, Joachim
Abstract: Introduction: Worldwide mass vaccination for COVID‐19 started in late 2020. COVID‐19 vaccines cause benign hypermetabolic lymphadenopathies. Clinical stratification between vaccine‐associated benign lymphadenopathies and malignant lymphadenopathies through ultrasound, MRI or FDG PET‐CT is not feasible. This leads to unnecessary lymph node biopsies, excisions and even radical lymph node dissections. Therefore, to avoid unnecessary surgeries, we assessed whether noninvasive multispectral optoacoustic tomography (MSOT) enables a better differentiation between benign and malignant lymphadenopathies. Patients and Methods: All patients were vaccinated for COVID‐19. We used MSOT to image deoxy‐ and oxyhaemoglobin levels in lymph nodes of tumour patients to assess metastatic status. MSOT imaging results were compared with standard ultrasound and pathological lymph node analysis. We also evaluated the influences of gender, age and time between vaccination and MSOT measurement of lymph nodes on the measured deoxy‐ and oxyhaemoglobin levels in patients with reactive lymph node changes. Results: Multispectral optoacoustic tomography was able to identify cancer‐free lymph nodes in vivo without a single false negative (33 total lymph nodes), with 100% sensitivity and 50% specificity. A statistically significant higher deoxyhaemoglobin content was detected in patients with tumour manifestations in the lymph node ( p  = 0.02). There was no statistically significant difference concerning oxyhaemoglobin ( p  = 0.65). Age, sex and time between vaccination and MSOT measurement had statistically non‐significant impact on deoxy‐ and oxyhaemoglobin levels in patients with reactive lymph nodes. Conclusion: Here, we show that MSOT measurement is an advantageous clinical approach to differentiate between vaccine‐associated benign lymphadenopathy and malignant lymph node metastases based on the deoxygenation level in lymph nodes.